Electrocatalytic urea mineralization in aqueous alkaline medium using NiIIcyclam-modified nanoparticulate TiO2 anodes and its relationship with the simultaneous electrogeneration of H2 on Pt counterelectrodes - Murcio Hernández, S.; Rueda Solorio, A.V.; Banda Alemán, J.A.; González Nava, C.; Rodríguez, F.J.; Bustos, E.; Espejel Ayala, F.; Rodríguez, A.; Sepúlveda, S.; Manríquez, J. (Elsevier, 2020)
NiIIcyclam-modified nanoparticulate TiO2-coated ITO electrodes (ITO/TiO2//NiIIcyclam) were prepared by electropolymerization of NiIIcyclam monomers to TiO2-coated ITO electrodes (ITO/TiO2) to improve electrocatalytic urea CO(NH2)2 oxidation in alkaline aqueous solutions. A high value adding secondary effect was the collection of electrons at Pt cathodes, to simultaneously generate H2 from water reduction. NiIIcyclam-modified ITO electrodes (ITO//NiIIcyclam) were also prepared by electropolymerization of NiIIcyclam monomers to bare ITO electrodes (ITO) for comparison purposes. In the presence of the TiO2 nanoparticles, the urea mineralization on NiIIcyclam coatings was doubled (23.95% – organic carbon removal at 120 min of electrolysis) compared to those without TiO2 nanoparticles (13.02% – organic carbon removal at 120 min of electrolysis). In agreement, the faradaic efficiency for H2 generation at the Pt cathode, electrically connected to an anode having TiO2 nanoparticles (0.99 at 120 min of electrolysis), was also twice as effective than that observed when the same Pt cathode was electrically connected to an anode without TiO2 nanoparticles (0.46 at 120 min of electrolysis). The experimental results indicated that the poisoning of NiII centers (which is caused by an excessive production of CO intermediates during the urea oxidation on both NiIIcyclam-modified anodes) was strongly inhibited in the presence of the nanoparticulate TiO2|NiIIcyclam junction. A final comparison between our results and those reported in selected publications revealed that the NiIIcyclam-modified nanoparticulate TiO2-coated ITO anodes here developed, constitutes a promising electrocatalytic system for performing direct urea mineralization at a relative short lectrolysis time. Furthermore, the combination of the following phenomena: (a) effective charge separation on the semiconducting ITO|nanoparticulate TiO2 junctions, (b) remarkable capabilities of the nanoporous TiO2 films for tuning the load of OH anions demanded by the urea oxidation and, (c) outstanding capabilities of the TiO2 nanoparticles for capturing CO intermediates (at Ti3+ donor sites), successfully promoted the enhancement of the electron external transport to Pt cathodes, and consequently improved the faradaic efficiency associated to the cathodic generation of H2.